Barcoding of Fin Clip Samples Revealed High Exploitation of Plectropomus leopardus in Spermonde Archipelago - Nuryanto, Agus; Pramono, Hendro; Kusbiyanto, Kusbiyanto; Ghifari, Muhammad Iqbal; Andareswari, Novi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Spermonde Archipelago in South Sulawesi is among groupers sources in Indonesia for International Marine Live Trade. It was not much known which species are mostly exploited in those areas during the study because only fin clip samples could be obtained. Here we performed DNA forensic analysis to groupers fin clips collected from Spermonde Archipelago using barcode marker to know what species were exploited and which ones was the most exploited species. A total of 110 fin clip samples were obtained during the field trips. Sequencing of the cytochrome c oxidase 1 gene was successful for only 36 samples. Species determination was based on sequences similarity to conspecific sequence available in barcoding of life database (BOLD). BOLD similarity test placed the 36 fin clip samples into four different species, namely Cromileptes altivelis, Epinephelus ongus, Plectropomus leopardus, and Plectropomus maculatus. The K-2P taxonomic tree showed clear separation among species which was supported by high K2P genetic distances among species. Most of fin clips were identified as Plectropomus leopardus indicates that this species was the most exploited in Spermonde Archipelago. This proved that molecular identification not only can be used to biodiversity study in certain area but also in forensic analysis of a threatened wildlife. This study has important contribution for conservation effort of those groupers species, especially P. leopradus and provides new approach for taxonomist and conservation managers to identify samples, especially when only incomplete specimens are available.